2002
DOI: 10.1074/jbc.m104347200
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of HECT-domain Ubiquitin Ligase hHYD and DNA Topoisomerase II-binding Protein for DNA Damage Response

Abstract: Ubiquitin ligases define the substrate specificity of protein ubiquitination and subsequent proteosomal degradation. The catalytic sequence was first characterized in the C terminus of E6-associated protein (E6AP) and referred to as the HECT (homologous to E6AP C terminus) domain. The human homologue of the regulator of cell proliferation hyperplastic discs in Drosophila, designated hHYD, is a HECT-domain ubiquitin ligase. Here we show that hHYD provides a ubiquitin system for a cellular response to DNA damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
108
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 32 publications
(37 reference statements)
0
108
0
Order By: Relevance
“…For example, expression of ERCC1 and XPA, components of the nucleotide excision repair pathways, are associated with platinum resistance in ovarian cancer (Damia et al, 1998;Selvakumaran et al, 2003); methylation and silencing of the mismatch repair gene MLH1 in some ovarian cancers also result in loss of cisplatin sensitivity (Strathdee et al, 1999); and disruption of the FANC/ BRCA pathway by methylation of BRCA1 and FANCF alters sensitivity to cisplatin in ovarian cancer (Taniguchi et al, 2003). As one function of EDD is in the cellular response to DNA damage (Henderson et al, 2002(Henderson et al, , 2006Honda et al, 2002;Munoz et al, 2007), we postulated that the ability of EDD to predict disease recurrence in serous ovarian cancer might similarly be related to the emergence of chemoresistance. The survival curves for those patients who initially responded to treatment were consistent with this hypothesis: all of the patients had a similar survival rate until approximately 12 months (disease recurrence) before diverging into two groups based on EDD expression with clearly different outcomes, suggestive of the emergence of chemoresistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, expression of ERCC1 and XPA, components of the nucleotide excision repair pathways, are associated with platinum resistance in ovarian cancer (Damia et al, 1998;Selvakumaran et al, 2003); methylation and silencing of the mismatch repair gene MLH1 in some ovarian cancers also result in loss of cisplatin sensitivity (Strathdee et al, 1999); and disruption of the FANC/ BRCA pathway by methylation of BRCA1 and FANCF alters sensitivity to cisplatin in ovarian cancer (Taniguchi et al, 2003). As one function of EDD is in the cellular response to DNA damage (Henderson et al, 2002(Henderson et al, , 2006Honda et al, 2002;Munoz et al, 2007), we postulated that the ability of EDD to predict disease recurrence in serous ovarian cancer might similarly be related to the emergence of chemoresistance. The survival curves for those patients who initially responded to treatment were consistent with this hypothesis: all of the patients had a similar survival rate until approximately 12 months (disease recurrence) before diverging into two groups based on EDD expression with clearly different outcomes, suggestive of the emergence of chemoresistant cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is no evidence that these proteins are ubiquitinylation substrates of EDD. Others have identified topoisomerase IIb-binding protein, required for cell survival after DNA damage (Yamane et al, 2002) and associated with an increased risk of familial breast and ovarian cancer (Karppinen et al, 2006), as a ubiquitinylation target of EDD (Honda et al, 2002).…”
mentioning
confidence: 99%
“…This property suggests that the EDD gene might play a role in human cancer. Our interest in this possibility was strengthened by recent evidence that EDD interacts with one or more proteins in the DNA damage response (Henderson et al, 2002;Honda et al, 2002). As an initial approach to evaluate EDD's involvement in cancer, we used microsatellite allelotyping to examine a narrow region of chromosome 8q that encompasses the locus for EDD (8q22.3) and identified this as a significant and specific area of allelic imbalance in ovarian cancer, hepatocellular carcinoma, squamous cell carcinoma of the tongue, breast cancer and metastatic melanoma.…”
Section: Discussionmentioning
confidence: 95%
“…This possibility is reinforced by an implied role for EDD in DNA damage signalling. A recent study found that topoisomerase IIb binding protein (TopBP1) is ubiquitinylated and targeted for proteosomal degradation by EDD (Honda et al, 2002). TopBP1 colocalizes with BRCA1 at stalled replication forks, evidence that TopBP1 functions in the DNA damage response (Makiniemi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The mammalian orthologue E3 identified by Differential Display (EDD) was first discovered through the use of differential display to identify progestin-regulated genes in a breast cancer cell line (23). Evidence suggesting an involvement of EDD1 in human cancer includes the finding from several studies demonstrating that the degree by which EDD1 interacts with CIB, TOPBP1, and CHK2 is regulated by the DNA damage response (22,24,25). Moreover, EDD1 expression has been shown to functionally correlate with the responsiveness of patients with ovarian cancer to DNA-damaging cytotoxic therapies (26).…”
Section: Discussionmentioning
confidence: 99%